Bibliometric Analysis Using VOSviewer with Publish or Perish of CEFR-based Comparison of English Language Teaching Models for Communication - Nadtayay, Nawaporn; Wongsaphan, Montree (Bumi Publikasi Nusantara, 2025)
This article aims to synthesize research related to the use of CEFR-based Comparison of English language teaching models for communication at the primary school level from 2020-2024 using the bibliometric analysis method assisted by mapping analysis. The data sources were taken from the Google Scholar database for the period 2020 - 2024. A total of 500 documents were found in the last 5 years. According to the research results, the number of publications on statistical significance testing both increases and decreases every year. From a total of 500 documents, as follows: in 2020 there were 86 related research papers, in 2021 there were 98 papers, in 2022 there were 103 papers, in 2023 there were 81 papers and related papers in 2024 there were 16 papers. The results of Article data maps produce three visualizations: network visualization, overlay, and density visualization. The mapping results show that statistical research is still needed, especially CEFR-based comparison of English language teaching models for communication at the primary school level. This study concludes that the research trend discussing statistics is decreasing CEFR-based comparison of English language teaching models. Although in terms of use, it is still very important. This is especially true for processing quantitative research data.